Dentin hypersensitivity and laser therapy - Alves , Keila de Souza; Moraes , Daniela Abreu de (Seven Editora, 2023)
Dentin hypersensitivity is considered an acute pain of short duration, resulting from the exposure of open dentinal tubules to the oral environment in response to mechanical, thermal, chemical and osmotic stimuli. Among the various treatments available, hypersensitivity can be treated with specific dentifrices, fluoride, desensitizers, adhesive systems and also through laser therapy. Laser therapy has been increasingly used for therapeutic purposes in dentistry, with properties such as photobiostimulation, photobiomodulation, analgesia and anti-inflammatory action. The objective of this work was to demonstrate, through a literature review, the scientific basis and clinical studies that support the use of lasers for the treatment of cervical dentin hypersensitivity. For its elaboration, articles were selected in the databases: PubMed, Virtual Health Library (Medline/LILACS/BBO), Science Direct, applying the following search descriptors in Portuguese “hypersensitivity”, “lasertherapy”, “dentinal tubules”, “ pain”, “non-carious cervical lesions”, in English “Dentin hypersensitivity”, “Non-carious cervical lesion” and “laser”. Based on the reading of titles and abstracts, and considering the following inclusion criteria: literature review articles, systematic review, randomized clinical trials and laboratory studies reporting on the use of laser published in the period from 2015 to 2021. The excluded works were unavailable articles in full, monographs, studies with incomplete methodology, dissertation and thesis. DOI:https://doi.org/10.56238/innovhealthknow-044